2022
DOI: 10.1038/s43247-022-00563-x
|View full text |Cite
|
Sign up to set email alerts
|

Heat flux assumptions contribute to overestimation of wildfire smoke injection into the free troposphere

Abstract: Injections of wildfire smoke plumes into the free troposphere impact air quality, yet model forecasts of injections are poor. Here, we use aircraft observations obtained during the 2019 western US wildfires (FIREX-AQ) to evaluate a commonly used smoke plume rise parameterization in two atmospheric chemistry-transport models (WRF-Chem and HRRR-Smoke). Observations show that smoke injections into the free troposphere occur in 35% of plumes, whereas the models forecast 59–95% indicating false injections in the si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 47 publications
1
16
0
Order By: Relevance
“…Taking four observed cases of smoke reaching into the free troposphere identified by Thapa et al. (2022), the vertical distribution of fire emissions was constrained with an inversion system used to assimilate HSRL observations. These constrained runs were compared to base runs using the Freitas et al.…”
Section: Emerging Results From Firex‐aqmentioning
confidence: 99%
See 3 more Smart Citations
“…Taking four observed cases of smoke reaching into the free troposphere identified by Thapa et al. (2022), the vertical distribution of fire emissions was constrained with an inversion system used to assimilate HSRL observations. These constrained runs were compared to base runs using the Freitas et al.…”
Section: Emerging Results From Firex‐aqmentioning
confidence: 99%
“…Thapa et al. (2022) took a closer look at the commonly used plume rise parameterization in WRF‐Chem and HRRR‐Smoke from Freitas et al. (2007).…”
Section: Emerging Results From Firex‐aqmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the errors in modeled thermodynamic structure and PBL heights can contribute to uncertainties in the inversely estimated injection fraction. In the recent study for all fire events sampled by FIREX-AQ in the western U.S. (Thapa et al, 2022), the underestimated PBL heights are found to be one of the key reasons of the more frequent free-troposphere injection cases modeled by WRF-Chem than observed. Taking the errors in modeled PBL heights into consideration, we examine the adjusted injection fractions (f >PBL,adj ) by using the corrected PBL heights based on DIAL-HSRL data.…”
Section: Constrained Smoke Emissions and Free-troposphere Smoke Injec...mentioning
confidence: 98%